2016
DOI: 10.1039/c6tc01718e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic graphene@PANI@porous TiO2 ternary composites for high-performance electromagnetic wave absorption

Abstract: A two-step strategy combining in situ polymerization and a hydrothermal process has been developed for coupling polyaniline (PANI) with porous TiO 2 anchored on magnetic graphene. The microstructure and morphology of magnetic graphene@PANI@porous TiO 2 were characterized by FETEM, FESEM, XRD, XPS and VSM in detail. The results indicated that magnetic graphene@PANI was completely covered by porous TiO 2 with random orientations and the saturation magnetization value of the composite was 19.2 emu g À1 . PANI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(88 citation statements)
references
References 62 publications
4
83
0
1
Order By: Relevance
“…In addition, the moderate attenuation constant and impendence matching also make the TF@PPy composite a prospect candidate for the excellent MA material (Figure S4, Supporting Information). Compared with other relative absorbers ( Table ), the hierarchical TF@PPy composite demonstrates considerable merits such as enhanced absorption properties, adjustable absorption frequency, and thin coating thickness (Figure g–i), which cater to the requirements of wider applicability in the microwave absorption . As mentioned above, the involved microwave absorption mechanisms can be divided into the following aspects ( Scheme ): a)Polarization loss: By comparing with TiO 2 @Fe 3 O 4 , the complex permittivity of TF@PPy increases significantly, demonstrating the excellent dielectric properties (Figure a,b).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the moderate attenuation constant and impendence matching also make the TF@PPy composite a prospect candidate for the excellent MA material (Figure S4, Supporting Information). Compared with other relative absorbers ( Table ), the hierarchical TF@PPy composite demonstrates considerable merits such as enhanced absorption properties, adjustable absorption frequency, and thin coating thickness (Figure g–i), which cater to the requirements of wider applicability in the microwave absorption . As mentioned above, the involved microwave absorption mechanisms can be divided into the following aspects ( Scheme ): a)Polarization loss: By comparing with TiO 2 @Fe 3 O 4 , the complex permittivity of TF@PPy increases significantly, demonstrating the excellent dielectric properties (Figure a,b).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the resonance was observed to rise with an increase in the amount of C-Fe 3 O 4 loaded in the PVDF matrix. This finding suggested that multiple polarization mechanisms occur in the samples with alteration of the EM field frequency [27]. Firstly, electron mobility between Fe 2+ and Fe 3+ ions as the wave travel within the material can generate dipole polarization.…”
Section: Em Wave Absorption Propertiesmentioning
confidence: 95%
“…However, the single ferrites cannot meet the increasingly high requirements for absorbing materials. The hybrid materials are widely regarded as ideal candidates for the absorbing application …”
Section: Introductionmentioning
confidence: 99%
“…The hybrid materials are widely regarded as ideal candidates for the absorbing application. [22][23][24] Graphene is a new member of the carbon family, but has attracted worldwide attention since its discovery in 2004. Graphene possesses great electronic, mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%